Hyperbaric Oxygenation in the Treatment of Fournier's Gangrene: A Systematic Review - Schneidewind, Laila (Urol Int, 2021)
INTRODUCTION: Fournier's gangrene (FG) is a sporadic, life-threatening, necrotizing infection affecting the perineum, perineal region, and genitals. Hyperbaric oxygenation (HBO) improves tissue perfusion and promotes angiogenesis and collagen synthesis. Despite these positive effects of HBO, the indication and the effects on outcome as adjunct therapy in FG remain controversial. Consequently, we decided to perform a systematic review to compare the treatment of FG with or without the use of HBO as an adjunct therapy. MATERIALS AND METHODS: We performed a systematic review following the recommendations provided in the Cochrane Handbook of systematic Reviews and the PRISMA reporting guidelines. Due to the paucity of data and a suspected lack of randomized controlled trials, we considered all the available information for this systematic review. RESULTS: The literature search for primary studies yielded 79 results. Finally, 13 studies were considered, which included a total of 376 patients with FG, of whom 202 received HBO therapy. Five of these studies had a retrospective case-control design. However, these 5 studies included a total of 319 patients; 145 of these patients were treated with adjunct HBO therapy. Overall, this leads to a mortality rate of 16.6% in the HBO group and 25.9% in the non-HBO group. Overall, risk of bias was assessed as moderate to high. CONCLUSIONS: We conclude that despite the risk of bias, HBO has potential as an adjunct in FG treatment, but it is challenging to carry out further studies, mainly due to the rareness of FG and availability of HBO.